PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS PENDAPATAN DAN PENGELOLAAN PASAR KOTA PAGAR ALAM - kamsrin Sa'i (JURNAL KOMPETITIF, 2012)
This study evaluated the effect of basically Leadership Styles and Work Motivation of Employee Performance Management Market Revenue Service and Pagaralam. And Management Revenue Service Pagaralam City Market is one of the offices under the auspices of the City of Pagaralam has a daunting task, one program is a mainstay of regional autonomy in carrying out all it can increase the motivation of people in development through payment of taxes and levies.Research hypotheses:1. Manager's leadership has a positive effect on employee performance.2. Motivation has a positive effect on employee performance.3. Manager leadership and employee motivation are common - both have a positive impact on employee performance. Used in this study Saturated Probability Sampling. This technique is used for all members of the population is used as a sample. While the design of this study is the influence of relationship between variables - variables using the survey method is to look at the influence of independent variables consisting of the leadership style (X1), motivation (X2) with variable attached to the performance (Y) Employees Revenue Service and Market Management Pagaralam city.Overall, the results of the study was based on leadership styles and motivation to work, either partially or themselves - individually or simultaneously to influence employee performance quite significantly. Key Word: Style Leadership, Work motivation, performance